The Impact of E-Service Quality and Sales Promotion on Purchase Decisions in the Zalora Online Shopping Application (Case Study on Zalora Consumers in Surabaya) - Indah Oktavianti Mulia; Zumrotul Fitriyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to examine the impact of e-service quality and sales promotion on Surabaya consumers' purchasing decisions on the online shopping application Zalora. This study's population comprises Surabaya residents who have utilized the Zalora online shopping application. This method employs quantitative research. Non-probability sampling with a purposive sampling technique yielded 99 respondents, and the Partial Least Square (PLS) method was utilized for data analysis. The findings of this study indicate that 1) e-service quality has a positive and statistically significant impact on purchasing decisions. 2) sales promotion has a significant and positive impact on purchasing decisions.